The Emigrant and Exiled Woman as Custody of Galician Historical Memory. The Case of the Process to José Mejuto Bernárdez, Republican Shot in 1937 - Mejuto Soba, Ana Paula; Rodríguez González, Olivia (Madrygal. Revista de Estudios Gallegos, 2017)
José Mejuto Bernárdez (1906-1937), a ship mechanic from Cangas do Morrazo, was involved in a military process as a result of the political repression in Galicia during the Spanish Civil War (1936-1939). Before being shot, he wrote about thirty letters from prison. His female relatives became relevant as guardians of the memory; they travelled in the early 50s from Galicia to Buenos Aires, in a sort of migration hiding another form of republican exile. With the aid of Rhetoric we will carry out a confronted reading of the most relevant moments of the process as shown both in the documents of the War Council and in the letters that Mejuto sent from prison.